Correlation Between Chlamydia pneumoniae Infection and Lipid Profile in Patients with Cardiovascular Diseases - Al. Halbosiy, Mohammed M. F.; Ismael, May K.; Nasser, Hadeel A. (Iraqi Journal of Science, 2019)
Cardiovascular disease (CVD) is a class of diseases that involve the blood vessels or heart. Chlamydia pneumoniae has been considered as the most reasonable; also, it is able to increase and persevere inside vascular cells and to make the chronic inflammation in atherosclerosis. In this study, blood samples were subjected for molecular detection of Chlamydia pneumoniae by using conventional polymerase chain reaction (PCR) depending on 16S rRNA. Seventy patients who suffer from cardiovascular diseases (angina, myocardial infarction and atherosclerosis) aged between 33-86 years have been investigated and compared to twenty of apparently healthy individuals were studied as a control group. Twenty-six samples (37.14) % revealed positive results for Chlamydia pneumoniae by PCR technique in blood samples of patients group, while all control samples were negative. No significant relationship was found among HDL,LDL, cholesterol, but the significant differences in the levels of triglyceride, VLDL between Chlamydia pneumoniae positive and negative within the patients' group were significant (P<0.05).The result of this study revealed that there was elevation of cholesterol and triglycerides level in patients their ages less than 50 years compared with other age groups although there was no significant relationship between HDL VLDL,LDL and age ; but generally certain patients with more than 60 years have the highest level of HDL VLDL, LDL.